Job Embeddedness as a Mediator of the Relationship between Organizational Justice and Employee Retention - Angel Christmas Thania Ginting; Yolla Margaretha (Jurnal Informatika Ekonomi Bisnis, 2026)
Employee retention has become an increasing concern in healthcare institutions facing workforce instability and persistent turnover challenges. This study examines the relationship between organizational justice and employee retention through the mediating role of job embeddedness among nurses at Hospital X in Bandung. While fairness perceptions shape employees evaluation of organizational practices, retention decisions are often influenced by the extent to which employees feel socially and psychologically connected to their workplace. Using a quantitative survey design, this research targeted 202 permanent nurses selected through purposive sampling; however, 220 valid responses were successfully collected and analyzed. Data were processed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. Analytical procedures included measurement model validation, structural model assessment, and bootstrapping to examine direct and indirect relationships. The results show that organizational justice does not significantly influence employee retention through a direct pathway. Its contribution emerges indirectly by strengthening job embeddedness, which subsequently increases employees’ intention to remain in the organization. Nurses who perceive equitable treatment are more likely to develop stronger workplace attachment, organizational fit, and perceived sacrifice associated with leaving. Job embeddedness therefore acts as a full mediator linking fairness perceptions to retention outcomes. These findings suggest that retention initiatives in hospital settings should extend beyond formal fairness practices. Building meaningful interpersonal connections, reinforcing organizational fit, and cultivating stronger attachment to the work environment may offer a more sustainable strategy for maintaining nursing workforce stability.